Selection of fermentation condition for expression of recombinant single chain antibody recognizing the antigen of blood type a in Escherichia coli - Ngoc Ha, Dang Thi; Trung, Nguyen Thi; Thu Hong, Le Thi; Huyen, Do Thi; Hai, Truong Nam (Academia Journal of Biology, 2017)
Single chain recombinant antibody identifying blood group A antigen in the ABO system (antiA_scFv) was constructed to express in E. coli. In this study, we optimized fermentation conditions to increase the yield of antiA_scFv expression as well as to reduce cost and save culture time. The results showed that the antiA_scFv expression was highest in the culture TB medium with 0.1 mM IPTG, at 30oC. Induction time point was in exponential growth phase of cells at the cell density OD600 = 1.5. With the selected fermentation conditions, the cell biomass increased 5.2 times (from OD600 = 3.27 to OD600 = 17.02) and antiA_scFv yield increased significantly as compared to the initial conditions.   Citation: Dang Thi Ngoc Ha, Le Thi Thu Hong, Do Thi Huyen, Truong Nam Hai, 2017. selection of fermentation condition for expression of recombinant single chain antibody recognizing the antigen of blood type a in escherichia coli. Tap chi Sinh hoc, 39(2): 204-211. DOI: 10.15625/0866-7160/v39n2.8485 *Corresponding author: tnhai@ibt.ac.vn Received 11 July 2016, accepted 20 March 2017